Stable hydrophobic silica aerogel particles and methods for making same
Patent Information
- Application Number
- CN202411037575.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-07-31
AI Technical Summary
Existing technologies make it difficult to prepare stable hydrophobic silica aerogel particles in alcohol solvent systems, and the control and penetration of modifiers are difficult, making it difficult to balance hydrophobic stability and thermal insulation performance.
By constructing a reasonable alcohol-water system, controlling the ratio of methyl and ethoxy groups in the modifier, and using supercritical ethanol drying technology to control the relative content of hydrophobic groups on the surface of silica aerogel particles, stable hydrophobic silica aerogel particles were prepared.
Silica aerogel particles with good porosity, thermal conductivity and excellent hydrophobic stability were obtained, which are suitable for industrial production. The porosity is above 90%, the thermal conductivity is below 0.03 W/(m·K), the water absorption rate is below 5%, and the stability is good.
Smart Images

Figure BDA0004971512490000081 
Figure BDA0004971512490000091 
Figure BDA0004971512490000092
Abstract
Description
Technical Field
[0001] This invention belongs to the field of silica aerogel technology, specifically relating to a stable hydrophobic silica aerogel particle material and its preparation method. Background Technology
[0002] Silica aerogel, as a novel nanoporous material, has shown broad application prospects in numerous fields due to its unique structure and excellent performance. This material is renowned for its low density, high transparency, and controllable structural characteristics. Its basic framework consists of silica nanoparticles filled with air, forming a highly porous network structure. This structure not only gives silica aerogel a lightweight appearance but also endows it with excellent adsorption capacity and thermal insulation properties. It shows broad application prospects in environmental protection, construction, optics, electronics, catalysis, and medicine.
[0003] Currently, silica aerogel materials are mainly in powder form, with granular silica aerogels being less common. Specimen silica aerogels generally refer to silica aerogel materials with a particle size of 1 mm or larger. Due to their characteristics of less dust release and more packing pores, granular silica aerogels have increasingly wider applications in industry. However, the preparation process of silica aerogel particles is relatively complex and they are easily broken, posing many challenges to industrial production. Surface modification of silica aerogel particles is also difficult, and the control and penetration of modifiers are even more challenging, requiring higher standards in terms of hydrophobicity and stability.
[0004] In hydrophobic modification, modifiers such as methylsilanes are commonly used to modify aerogels. Modified aerogels not only exhibit enhanced hydrophobicity but also improved thermal stability and extended service life. The effect of hydrophobic modification is often roughly assessed by measuring the hydrophobic angle after modification, and the results are explored through simple variations in the type and amount of modifier. However, this assessment is often delayed and it is difficult to achieve a balanced improvement in hydrophobic modification results and other properties such as thermal insulation. Especially for particulate silica aerogels, on the one hand, to ensure the stability of the silica aerogel particle morphology, the preparation process needs to be carried out in an alcohol solvent system. Alcohols, especially ethanol, in the alcohol solvent system can easily cause significant changes in the occupancy of the modifying groups. On the other hand, the particle morphology alters the adhesion and exposure of the modifier on the particle surface, affecting the relative changes in the hydrophobic groups and causing unpredictable impacts on the hydrophobic modification effect, stability, and thermal insulation. For example, in terms of hydrophobic stability, the poor hydrophobic stability is often due to the influence of the alcohol solvent system between the above-mentioned particle structures and the changes in the microenvironment. Summary of the Invention
[0005] In view of the above-mentioned problems of the prior art, the present invention discloses the influence of different modifier groups on the surface properties of silica aerogel in an alcohol solvent system, and successfully obtains stable hydrophobic silica aerogel particles by means of group regulation.
[0006] This invention discloses stable hydrophobic silica aerogel particles, comprising a silicon source, a modifier, a catalyst, ethanol, and water; wherein the molar ratio of ethanol to water is (1-10):1, the molar ratio of silicon source to alcohol is 1:(80-150), and the molar amount of methyl groups A in the raw materials is... CH3 The molar amount A of ethoxy groups other than ethanol solvent in the raw material OCH2CH3 The ratio is A CH3 :A OCH2CH3 =(4-35):100; silica aerogel particles 13 In the carbon NMR spectrum, the peak area of the methyl group is I. CH3 Peak area of ethoxy group I OCH2CH3 The ratio is 0.5 ≤ I CH3 :I OCH2CH3 ≤6.
[0007] In some embodiments, the molar ratio of ethanol to water in the raw materials of this invention is (2-5):1, the molar ratio of silicon source to alcohol is 1:(100-150), and the molar amount of methyl group A in the raw materials is... CH3 The molar amount A of ethoxy groups other than ethanol solvent in the raw material OCH2CH3 The ratio is A CH3 :A OCH2CH3 =(4-35):100; silica aerogel particles 13 In the carbon NMR spectrum, the peak area of the methyl group is I. CH3 Peak area of ethoxy group I OCH2CH3 The ratio is 3≤I CH3 :I OCH2CH3 ≤6.
[0008] In some embodiments, the silicon source includes one or more of tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), polysiloxane (PEDS), etc.
[0009] In some formulations, the modifier includes one or more of methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylmethoxysilane (TMSOME), trimethylchlorosilane (TMCS), and hexamethyldisiloxane (HMDSO).
[0010] In some schemes, the catalyst includes one or more of acid catalysts, base catalysts, and acrylate catalysts; wherein the acid catalyst includes hydrochloric acid, ammonium chloride, and ammonium fluoride, the base catalyst includes ammonia, LiOH, NaOH, and KOH, and the acrylate catalyst includes 3-(trimethoxysilyl)propyl methacrylate (TMSPM).
[0011] In some schemes, the molar ratio of catalyst to silicon source is 0.1% to 10%.
[0012] In some schemes, the catalyst is a composite catalyst of ammonium fluoride and ammonia, with the molar ratio of ammonium fluoride and ammonia relative to the silicon source being 2% to 8%.
[0013] The present invention also provides a method for preparing the above-mentioned stable hydrophobic silica aerogel particles, comprising the following steps:
[0014] S1: Prepare silica sol using silicon source, modifier, ethanol, and water according to the metering ratio;
[0015] S2: Prepare wet gel by adding catalyst to silica sol according to the stoichiometric ratio;
[0016] S3: The wet gel is crushed and sieved to obtain wet gel particles that meet the particle size requirements;
[0017] S4: Aging the wet gel to obtain aged particles;
[0018] S5: The aged particles are subjected to supercritical ethanol drying. The supercritical temperature of ethanol is reached at a heating rate of 40-85℃ / h, while the pressure is increased to 5-10MPa. The temperature is maintained for more than 1 hour, and the product is obtained after depressurization and cooling.
[0019] In some solutions, the preparation process of the silica sol in step S1 is as follows: first, mix ethanol and water evenly, then add the silicon source and modifier to the alcohol-water mixture and continue stirring until evenly mixed.
[0020] In some embodiments, the catalyst in step S2 is added after being prepared in the form of an aqueous solution, and the molar concentration of the catalyst in the aqueous solution is 0.01-1 mol / L.
[0021] In some embodiments, in step S2, the silica sol is first mixed evenly with an ammonium fluoride aqueous solution, and then an ammonia aqueous solution is added and stirred to obtain the final product.
[0022] In some schemes, in step S3, the particle size of the wet gel particles after crushing and sieving is not less than 1 mm.
[0023] In some embodiments, in step S4, the aging solution for the aging treatment is one or a mixture of methanol, ethanol, isopropanol, and hexamethyldisilazane (HMDS).
[0024] In some schemes, in step S4, the aging treatment temperature is 25℃-70℃ and the time is 1-48h.
[0025] In some schemes, the holding time for supercritical drying of ethanol in step S5 is 1-6 hours.
[0026] Compared with the prior art, the present invention has at least the following beneficial effects:
[0027] This invention successfully obtained particulate silica aerogel material with good porosity, thermal conductivity, and excellent hydrophobicity and stability by constructing a reasonable alcohol-water system environment, controlling the proportion of selective hydrophobic groups in the aerogel feed, and controlling the relative content of selective hydrophobic groups on the surface of silica aerogel particles through supercritical ethanol drying.
[0028] The silica aerogel obtained by this invention has a particle size of more than 1 mm, a porosity of more than 90%, a thermal conductivity of less than 0.03 W / (m·K), a water absorption rate of no more than 5% in 1 day, and a water absorption rate change of no more than 0.5% in 7 days, and has wide application value.
[0029] The preparation process of the material of this invention is simple and controllable, environmentally friendly, and conducive to large-scale industrial production. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 The silica aerogel particles obtained by nuclear magnetic resonance detection according to this invention 13 C. Spectrum. Where A is the spectrum curve of Comparative Example 1, B is the spectrum curve of Comparative Example 2, and C is the spectrum curve of Example 2. Detailed Implementation
[0032] The embodiments of the present invention are merely some, not all, of the embodiments described herein. All other embodiments obtained by those skilled in the art based on the embodiments described herein without inventive effort are within the scope of protection of this application.
[0033] There are many types of hydrophobic modifiers for silica aerogels, including methylsilanes such as methyltrimethoxysilane (MTMS), trimethylchlorosilane (TMCS), trimethylmethoxysilane, and hexamethyldisiloxane (HMDSO); fluorinated silanes such as perfluorooctyltriethoxysilane (FAS-18) and perfluorodecyltriethoxysilane (FAS-17); organopolysiloxanes such as polydimethylsiloxane (PDMS) and polydiethoxysiloxane (PDEOS); silazanes such as hexamethyldisilazane (HMDS); and organosilicon resins. Different modifiers affect the hydrophobicity of aerogels through various mechanisms. For example, MTMS reacts with the silanol groups (Si-OH) on the aerogel surface to form hydrophobic Si-O-Si bonds, thereby improving the hydrophobicity of the aerogel. Fluorosilanes react with the silanol groups on the aerogel surface to form hydrophobic fluorinated surfaces, significantly improving the hydrophobicity of the aerogel. HMDS reacts with the silanol groups on the aerogel surface during modification to form hydrophobic Si-N bonds, and so on. It is evident that different hydrophobic modifiers, through different mechanisms of interaction and linkage relationships with the aerogel surface, bring about different hydrophobic effects.
[0034] Methyl and ethoxy groups, as different hydrophobic modification groups, play different roles in the modification effect. After methyl modification, the aerogel exhibits higher thermal stability during pyrolysis, which may be due to the introduction of methyl increasing the apparent activation energy of the aerogel material; while ethoxy shows stronger adsorption performance and hydrolysis resistance, which may be related to the specific chain length and oxygen-containing flexible group of ethoxy in the aerogel. The applicant found that by controlling the amount of methyl and ethoxy in the silica aerogel raw material in the alcohol solvent system, and regulating the relative change of methyl and ethoxy in the material system, the hydrophobicity of silica aerogel particles can be effectively improved, while improving the microenvironment between particles and the influence of interparticle gaps, thus improving the long-term stability of the material in hydrophobic and high-temperature environments.
[0035] Therefore, the stable hydrophobic silica aerogel particles proposed in this invention comprise raw materials including a silicon source, a modifier, a catalyst, ethanol, and water; wherein the molar ratio of ethanol to water is (1-10):1, the molar ratio of silicon source to alcohol is 1:(80-150), and the molar amount of methyl groups in the raw materials is A. CH3 The molar amount A of ethoxy groups other than ethanol solvent in the raw material OCH2CH3 The ratio is A CH3 :A OCH2CH3 =(4-35):100; silica aerogel particles 13 In the carbon NMR spectrum, the peak area of the methyl group is I. CH3 Peak area of ethoxy group I OCH2CH3 The ratio is 0.5 ≤ I CH3 :I OCH2CH3 ≤6.
[0036] The silica aerogel particles of this invention, by selecting a reasonable alcohol-water system (the molar ratio of ethanol to water is (1-10):1, and the molar ratio of silicon source to alcohol is 1:(80-150)), firstly provide a suitable ethanol environment for the silicon source gelation process. This constructs a suitable silicon source crosslinking environment, providing an environmental basis for the formation of aerogel particles. Secondly, it facilitates the binding of modifiers and corresponding methyl and ethoxy groups during the material gelation process, providing an environmental basis for group modification. Further control of A in the raw materials... CH3 and A OCH2CH3 The ratio of methyl and ethoxy groups modified to stabilize the aerogel surface is beneficial for constructing a surface bonding state that is suitable for hydrophobic properties while also considering stability. The resulting silica aerogel particles exhibit a favorable relative variation relationship (0.5 ≤ I) based on the above. CH3 :I OCH2CH3 ≤6), which ensures that the surface of the silica aerogel particles in the final state maintains a relatively stable surface state and amount of hydrophobic groups during the drying process. While improving hydrophobicity through methyl and ethoxy groups, it also effectively regulates the changes in the occupancy of modified groups in the alcohol solvent and their adhesion and exposure on the particle surface, greatly enhancing the hydrophobic properties of the product.
[0037] In some embodiments, the stable hydrophobic silica aerogel particles of the present invention comprise raw materials including a silicon source, a modifier, a catalyst, ethanol, and water; wherein the molar ratio of ethanol to water is (2-5):1, the molar ratio of silicon source to alcohol is 1:(100-150), and the molar amount A of methyl groups in the raw materials is... CH3 The molar amount A of ethoxy groups other than ethanol solvent in the raw material OCH2CH3 The ratio is A CH3 :A OCH2CH3 =(4-35):100; silica aerogel particles 13 In the carbon NMR spectrum, the peak area of the methyl group is I. CH3 Peak area of ethoxy group I OCH2CH3 The ratio is 3≤I CH3 :I OCH2CH3 ≤6. An optimized formulation system is beneficial for further improving the long-term stability of the material.
[0038] In some embodiments, the silicon source includes one or more of tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate (TMOS), and polysiloxanes (PEDS). Among these, the aerogel structure generated by the hydrolysis and condensation reaction of tetraethyl orthosilicate (TEOS) is complete, with a uniform and reasonable pore size distribution, which is conducive to building a stable microporous structure and is a more suitable silicon source material for the system of this invention.
[0039] In some formulations, the modifier includes one or more of methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylmethoxysilane (TMSOME), trimethylchlorosilane (TMCS), and hexamethyldisiloxane (HMDSO).
[0040] In the system of this invention, methyl and ethoxy groups (A CH3 A OCH2CH3 The sources of (A) include silicon sources and modifiers. For example, 1 mole of tetraethyl orthosilicate (TEOS) can provide 4 moles of ethoxy groups to the system, and 1 mole of methyltriethoxysilane (MTES) can provide 1 mole of methyl groups and 3 moles of ethoxy groups to the system. How can the appropriate addition and blending of materials in the system achieve the desired effect on A in the raw materials? CH3 A OCH2CH3 Control of molar quantity.
[0041] In some schemes, the catalysts include acid catalysts (such as hydrochloric acid, ammonium chloride, and ammonium fluoride), base catalysts (such as ammonia, LiOH, NaOH, and KOH), and acrylate catalysts (such as 3-(trimethoxysilyl)propyl methacrylate (TMSPM)). Among these, using ammonium fluoride and ammonia as a composite catalyst is more conducive to the full cross-linking of the aerogel in the system of this invention and the establishment of a stable pore structure, thus promoting the stability of the aerogel particles.
[0042] In some schemes, the molar ratio of the catalyst to the silicon source is 0.1% to 10%. When ammonium fluoride and ammonia are used as a composite catalyst, their molar ratios to the silicon source are preferably 2% to 8%, respectively.
[0043] This invention provides a method for preparing the above-mentioned stable hydrophobic silica aerogel particles, comprising the following steps:
[0044] S1: Prepare silica sol using silicon source, modifier, ethanol, and water according to the metering ratio;
[0045] S2: Prepare wet gel by adding catalyst to silica sol according to the stoichiometric ratio;
[0046] S3: The wet gel is crushed and sieved to obtain wet gel particles that meet the particle size requirements;
[0047] S4: Aging the wet gel to obtain aged particles;
[0048] S5: The aged particles are subjected to supercritical ethanol drying. The supercritical temperature of ethanol is reached at a heating rate of 40-85℃ / h, while the pressure is increased to 5-10MPa. The temperature is maintained for more than 1 hour, and the product is obtained after depressurization and cooling.
[0049] In the system of this invention, the I of silica aerogel particles CH3and I OCH2CH3 The ratio can be controlled through the supercritical drying process of ethanol. During supercritical drying, by changing the heating rate, pressure, and time, the relative content of ethoxy groups on the aerogel surface after ethanol is expelled from the aerogel pores can be altered, thereby controlling the relative content of methyl and ethoxy modifier groups.
[0050] In some solutions, the preparation process of the silica sol in step S1 is as follows: first, mix ethanol and water evenly, then add the silicon source and modifier to the alcohol-water mixture and continue stirring until evenly mixed.
[0051] In some embodiments, the catalyst in step S2 is added after being prepared in the form of an aqueous solution, and the molar concentration of the catalyst in the aqueous solution is 0.01-1 mol / L.
[0052] In some embodiments, in step S2, the silica sol is first mixed evenly with an ammonium fluoride aqueous solution, and then an ammonia aqueous solution is added and stirred to obtain the final product.
[0053] In some schemes, in step S3, the crushing and screening can be carried out using general crushing and screening equipment. This invention does not impose any restrictions. It is preferable that the particle size of the wet gel particles after screening is not less than 1 mm.
[0054] In some embodiments, in step S4, the aging solution for the aging treatment is one or a mixture of methanol, ethanol, isopropanol, and hexamethyldisilazane (HMDS), with ethanol being preferred in the system of the present invention.
[0055] In some schemes, in step S4, the aging treatment temperature is 25℃-70℃, and the time is 1-48h. This is beneficial for the full aging of the gel particles, resulting in structural stability and high aging efficiency.
[0056] In some schemes, the holding time for supercritical ethanol drying in step S5 is preferably 1-6 hours. This is beneficial for thorough drying while maintaining the integrity and stability of the particle surface, and also takes efficiency into account.
[0057] The present invention will be further described and verified in detail below through specific embodiments.
[0058] Example 1
[0059] An aqueous solution of ammonium fluoride with a molar concentration of 0.01 mol / L was prepared as catalyst 1, and an aqueous solution of ammonia with a molar concentration of 0.01 mol / L was prepared as catalyst 2.
[0060] Tetraethyl orthosilicate (TEOS), methyltriethoxysilane (MTES), anhydrous ethanol, and water were mixed and stirred evenly in a molar ratio of 1:0.2:150:65. Then, catalyst 1 was added and stirred, followed by catalyst 2. The amount of catalyst 1 and catalyst 2 added was 2% of the molar ratio of the silicon source.
[0061] The gelled material is crushed and sieved to obtain wet gel particles with a particle size of 1–10 mm.
[0062] Anhydrous ethanol was added to the wet gel particles, and then they were placed in an oven at 50°C for aging treatment for 48 hours.
[0063] The aged particles were subjected to supercritical ethanol drying at a heating rate of 65°C / h to reach 255°C, while simultaneously increasing the pressure to 8 MPa and holding at this temperature for 1 hour. After depressurization and cooling, the product of this invention was obtained. Nuclear magnetic resonance (NMR) analysis revealed the silica aerogel particles... 13 In the C spectrum, the peak area of the methyl group is I. CH3 Peak area of ethoxy group I OCH2CH3 The ratio is I CH3 :I OCH2CH3 =0.51.
[0064] Examples 2-9
[0065] Using the same method as in Example 1, but changing some parameters, different product examples of the present invention were obtained. The parameter changes are listed in Table 1.
[0066] Comparative Examples 1-4
[0067] Using the same method as in Example 1, but with some parameters changed, different comparative product cases were obtained. The parameter changes are also listed in Table 1.
[0068] Table 1
[0069]
[0070]
[0071] The products obtained from the above embodiments and comparative examples were tested.
[0072] Bulk porosity testing: The bulk density method was used. The prepared silica aerogel was finely ground and sieved to form a uniform powder. This powder was then placed in a 5 mL precision graduated cylinder and vibrated until the volume reading remained stable. The volume V was recorded at this point, and the mass M of the powder was weighed to obtain the bulk density P1 = M / V. The bulk porosity P was then obtained using the formula P = (1 - P1 / P0), where P0 is the theoretical density of silica.
[0073] Thermal conductivity testing: The silica aerogel product is sieved into a uniform powder and placed into the sample frame of the thermal conductivity meter. The sample is then covered with a thermocouple, and excess sample is scraped off. The cover plate is then installed. Under normal temperature and pressure conditions, the instrument testing system is allowed to stabilize, i.e., the change in thermal equilibrium is no greater than 0.01 units per minute, before the thermal conductivity test begins. The thermal conductivity λ is recorded after the test system displays a stable result.
[0074] Water absorption and stability: 1g of dried silica aerogel product was wrapped in a stainless steel mesh and placed in a 200ml container, ensuring the aerogel did not overflow. The container was then filled with water and sealed. One portion was left at room temperature for one day, after which the sample was removed, the outer moisture was wiped off, and the mass change was measured to obtain the 1-day water absorption rate. Another portion was placed in a constant temperature environment at 30℃ for 7 days, after which the sample was removed, the outer moisture was wiped off, and the mass change was measured to obtain the 7-day water absorption rate.
[0075] The test results are listed in Table 2.
[0076] Table 2
[0077]
[0078]
[0079] As can be seen from the results in Table 2 above, the silica aerogel materials obtained by this invention all possess good porosity and thermal conductivity, while exhibiting superior results in terms of hydrophobicity and stability. The changes in water absorption rate in Table 2 reflect the alteration of hydrophobicity of the aerogel particles under prolonged high-temperature conditions; a small change in water absorption rate indicates good hydrophobic stability of the material.
[0080] Examples 1-9 demonstrate that the silica aerogel product of the present invention has a porosity of over 90% and a thermal conductivity of less than 0.03 W / (m·K), meeting the needs of silica aerogels in various fields for thermal insulation. This is achieved by constructing a suitable ethanol environment during the silica source gelation process and simultaneously controlling the methyl A content in the raw materials. CH3 and ethoxy A OCH2CH3 The ratio can be further adjusted by regulating the operating regime of the ethanol supercritical drying process to control the relative changes in the amounts of methyl and ethoxy groups in the product, thereby achieving a synergistic improvement in hydrophobicity and stability. In the operating regime for controlling the ethanol supercritical drying process, we found that a faster heating rate is beneficial for improving I... CH3 and I OCH2CH3 The ratio is likely due to the fact that faster heating helps reduce the esterification reaction, decreasing the conversion of residual hydroxyl groups to ethoxy groups, while higher pressure reduces I... CH3 and I OCH2CH3The ratio is likely due to the fact that high pressure facilitates the bonding of ethoxy groups in the aerogel pores, more ethoxy residues are retained in the supercritical state of ethanol, and the effect of heating rate on the relative change of hydrophobic groups is more significant than the effect of pressure.
[0081] As shown in Examples 1-9 compared to Comparative Example 1, Comparative Example 1 introduced relatively fewer methyl groups into its raw materials through the silicon source and modifier. CH3 :A OCH2CH3 The prepared silica aerogel particles were at a lower level, and the I... CH3 :I OCH2CH3 The relative content of the components did not reach a suitable ratio, resulting in significant differences in the product's water absorption rate and stability.
[0082] As shown in Examples 1-9 compared to Comparative Example 2, an inappropriate heating regime caused I CH3 :I OCH2CH3 Inappropriate relative changes may improve short-term water absorption and reduce hydrophobicity, but they result in poor hydrophobic stability.
[0083] As shown in Examples 1-9 compared to Comparative Example 3, the raw materials contained less ethanol, resulting in an unsuitable ethanol environment. CH3 :I OCH2CH3 The relative change cannot achieve a suitable surface ratio between the two, and similarly, short-term hydrophobicity decreases, but long-term hydrophobic stability cannot be well improved.
[0084] As shown in Examples 1-9 compared to Comparative Example 4, excessive A in the raw materials CH3 :A OCH2CH3 This leads to an excessively high methyl content and competitive occupancy, I CH3 :I OCH2CH3 The water absorption rate is also too high. Although there is no significant change in hydrophobic stability, the overall improvement in hydrophobic effect is limited, and the water absorption rate is relatively high.
[0085] The technical features of the embodiments described above can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make modifications, alterations, substitutions, and variations to the above embodiments within the scope of the present invention. Furthermore, without contradiction, those skilled in the art can combine and integrate different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
Claims
1. A stable hydrophobic silica aerogel particle, comprising a silicon source, a modifier, a catalyst, ethanol, and water; wherein, The molar ratio of ethanol to water is (1-10):1, the molar ratio of silicon source to alcohol is 1:(80-150), and the molar amount of methyl groups in the raw material is A. CH3 The molar amount A of ethoxy groups other than ethanol solvent in the raw material OCH2CH3 The ratio is A CH3 A OCH2CH3 =(4-35): 100; silica aerogel particles 13 In the carbon NMR spectrum, the peak area of the methyl group is I. CH3 Peak area of ethoxy group I OCH2CH3 The ratio is 0.5 ≤ I CH3 : I OCH2CH3 ≤6; The stable hydrophobic silica aerogel particles are obtained by the following steps: S1: Prepare silica sol using silicon source, modifier, ethanol, and water according to the metering ratio; S2: Prepare wet gel by adding catalyst to silica sol according to the stoichiometric ratio; S3: The wet gel is crushed and sieved to obtain wet gel particles that meet the particle size requirements; S4: Aging the wet gel to obtain aged particles; S5: The aged particles are subjected to supercritical ethanol drying. The supercritical temperature of ethanol is reached at a heating rate of 40-85℃ / h, while the pressure is increased to 5-10MPa. The temperature is maintained for more than 1 hour, and the product is obtained after depressurization and cooling.
2. The stable hydrophobic silica aerogel particles according to claim 1, characterized in that, In the raw materials, the molar ratio of ethanol to water is (2-5):1, the molar ratio of silicon source to alcohol is 1:(100-150), and the molar amount of methyl in the raw materials is A. CH3 The molar amount A of ethoxy groups other than ethanol solvent in the raw material OCH2CH3 The ratio is A CH3 A OCH2CH3 =(4-35): 100; silica aerogel particles 13 In the carbon NMR spectrum, the peak area of the methyl group is I. CH3 Peak area of ethoxy group I OCH2CH3 The ratio is 3≤I CH3 : I OCH2CH3 ≤6.
3. The stable hydrophobic silica aerogel particles according to claim 1, characterized in that, The silicon source includes one or more of tetraethyl orthosilicate, methyl orthosilicate, and polysiloxane.
4. The stable hydrophobic silica aerogel particles according to claim 1, characterized in that, Modifiers include one or more of methyltrimethoxysilane, methyltriethoxysilane, trimethylmethoxysilane, trimethylchlorosilane, and hexamethyldisiloxane.
5. The stable hydrophobic silica aerogel particles according to claim 1, characterized in that, The catalyst includes one or more of acid catalysts, base catalysts, and acrylate catalysts; wherein, acid catalysts include hydrochloric acid, ammonium chloride, and ammonium fluoride, base catalysts include ammonia, LiOH, NaOH, and KOH, and acrylate catalysts include 3-(trimethoxysilyl)propyl methacrylate.
6. The stable hydrophobic silica aerogel particles according to claim 1, characterized in that, The molar ratio of the catalyst to the silicon source is 0.1% to 10%.
7. The stable hydrophobic silica aerogel particles according to claim 1, characterized in that, The catalyst is a composite catalyst consisting of ammonium fluoride and ammonia, with the molar ratio of ammonium fluoride and ammonia relative to the silicon source being 2% to 8%.
8. A method for preparing the stable hydrophobic silica aerogel particles according to any one of claims 1-7, comprising the following steps: S1: Prepare silica sol using silicon source, modifier, ethanol, and water according to the metering ratio; S2: Prepare wet gel by adding catalyst to silica sol according to the stoichiometric ratio; S3: The wet gel is crushed and sieved to obtain wet gel particles that meet the particle size requirements; S4: Aging the wet gel to obtain aged particles; S5: The aged particles are subjected to supercritical ethanol drying. The supercritical temperature of ethanol is reached at a heating rate of 40-85℃ / h, while the pressure is increased to 5-10MPa. The temperature is maintained for more than 1 hour, and the product is obtained after depressurization and cooling.
9. The preparation method according to claim 8, characterized in that, The preparation process of the silica sol in step S1 is as follows: first, mix ethanol and water evenly, then add the silicon source and modifier to the alcohol-water mixture and continue stirring until evenly mixed.
10. The preparation method according to claim 8, characterized in that, The catalyst in step S2 is added after it has been prepared in the form of an aqueous solution, and the molar concentration of the catalyst in the aqueous solution is 0.01-1 mol / L.
11. The preparation method according to claim 8, characterized in that, In step S2, silica sol is first mixed evenly with ammonium fluoride aqueous solution, and then ammonia aqueous solution is added and stirred to obtain the final product.
12. The preparation method according to claim 8, characterized in that, In step S3, the particle size of the wet gel particles after crushing and sieving is not less than 1 mm.
13. The preparation method according to claim 8, characterized in that, In step S4, the aging solution for aging treatment is one or a mixture of methanol, ethanol, isopropanol, and hexamethyldisilazane.
14. The preparation method according to claim 8, characterized in that, In step S4, the aging treatment temperature is 25℃-70℃ and the time is 1-48h.
15. The preparation method according to claim 8, characterized in that, In step S5, the holding time for supercritical drying of ethanol is 1-6 hours.
Citation Information
Patent Citations
Method for preparing silica aerogel and self-hydrophobic silica aerogel heat preservation felt pad through one-step technology
CN111039295A
Method for manufacturing aerogel blanket and aerogel blanket prepared therefrom
WO2022080721A1
